A study of the thermal degradation of model compounds of amine-cured epoxide resins - Percy, Vivienne Ann (Not Specified, 2024)
[page 49 missing] The thermal ciegradation of rr..odel compounds of a~ine-cur2d epoxide resins has been studied with the aim of investigating the thermal stability of the "cure-linkage". · 1, 3-Diphenoxypropan-2 ~ol and l-(N-ethylanilino)-3-phenoxypropan-2-ol have been synthesised and degraded m~er various conditions. The results of these degradations are presented and their relevance to t~1.e thermal dE:!gradation of amine-cured epoxide resins is discussed. The effect of the presence of alumina, which b.as been used as a filler for epoxide resins, on the thermal stability uf the model compounds has been examined. The possibility that the degradation of model compounds may be used as a synthetic route to benzofuran has been investigated.